How to assess the needs of vulnerable population groups towards heat-sensitive routing?: an evidence-based and practical approach to reducing urban heat stress - Foshag, Kathrin; Fürle, Johannes; Ludwig, Christina; Fallmann, Joachim; Lautenbach, Sven; Rupp, Saskia; Burst, Patrick; Betsch, Marco; Zipf, Alexander; Aeschbach, Nicole (Erdkunde, 2024)
Heat poses a significant risk to human health, particularly for vulnerable populations, such as pregnant women, older individuals, young children and people with pre-existing medical conditions. In view of this, we formulated a heat stress-avoidant routing approach in Heidelberg, Germany, to ensure mobility and support day-to-day activities in urban areas during heat events. Although the primary focus is on pedestrians, it is also applicable to cyclists. To obtain a nuanced understanding of the needs and demands of the wider population, especially vulnerable groups, and to address the challenge of reducing urban heat stress, we used an inter- and transdisciplinary approach. The needs of vulnerable groups, the public, and the city administration were identified through participatory methods and various tools, including interactive city walks. Solution approaches and adaptation measures to prevent heat stress were evaluated and integrated into the development of a heat-avoiding route service through a co-design process. The findings comprise the identification of perceived hotspots for heat (such as large public spaces in the city centre with low shading levels), the determination of commonly reported symptoms resulting from severe heat (e.g., fatigue or lack of concentration), and the assessment of heat adaptation measures that were rated positively, including remaining in the shade and delaying errands. Additionally, we analysed and distinguished between individual and community adaptation strategies. Overall, many respondents did not accurately perceive the risk of heat stress in hot weather, despite severe limitations. As a result, the heat-sensitive routing service (available in prototype form during publication) that has been created serves as a readily available and accessible source of assistance to combat the effects of heat stress in individuals' daily lives during periods of intense heat. The findings served as input for the calibration of heat stress-avoidant routing and supported the development of local heat protection plans without investing in large-scale adaptation of the built environment. It is crucial to involve the population, particularly vulnerable groups, in the development of the tool to ensure it meets their needs. This study employed a transdisciplinary multi-method approach, which considers practical framework conditions by involving the city administration.